Green synthesis of silver and copper nanoparticles using hydroxyethyl cellulose and its antibacterial activity - Sasikala, Appalasuwami (2018)
This dissertation is mainly focused about the introduction of a new method of synthesizing silver and copper nanoparticles (AgNPs and CuNPs) using hydroxyethyl cellulose (HEC). The study was done via green chemistry method to avoid the usage of some hazardous chemicals and also to save the cost of production. This thesis describes the optimal conditions for the synthesis of nanoparticles by analysing various parameters, such as the volume of the precursors silver nitrate (AgNO3) and copper nitrate (Cu(NO3)2), the concentration of HEC, reaction times and temperature. At 100 °C, the AgNPs reaction went to completion in 30 min while the CuNPs reaction about 3 min. The presence of both AgNPs and CuNPs were assured by ultraviolet visible spectroscopy (UV-Vis), which showed surface plasmon resonance (SPR) peaks at 410 - 430 nm and 550 - 600 nm respectively. The presence of the nanoparticles and the crystal structure were confirmed by X-ray diffractometry (XRD) and energy-dispersive X-ray (EDX). The structural and morphological characterisations of the AgNPs and CuNPs were performed using a transmission electron microscope (TEM) and field emission scanning electron microscope (FESEM). The antibacterial activities of the nanoparticles were also studied via the agar-well diffusion method, minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC). The research also tested the effects of AgNPs, CuNPs and Ag-CuNP mixtures on Gram-positive and Gram-negative bacteria. The nanoparticles showed good antibacterial activity against Bacillus subtilis (B. subtilis), Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa), Entercoccus faecalis (E. faecalis) and Staphylococcus aureus (S. aureus). The inhibition zones for these nanoparticles varied based on the type of bacteria. The larger inhibition zone was observed on Gram-negative bacteria (E. coli). The sizes of the said inhibition zones were 19 mm for AgNPs, 16 mm for CuNPs and Ag-CuNPs. Thus, it can be concluded that the invention of a feasible green method for the synthesis of AgNPs and CuNPs had a good inhibitory effect on the bacteria and hence, there are various potential applications for these nanoparticles.